State Financial Management During the Caliphate of Abu Bakr As-Siddiq: Historical Perspectives on Islamic Civilization and Its Relevance to Islamic Business Management - Ari Purwanto (EDUJAVARE: International Journal of Educational Research, 2026)
The death of Prophet Muhammad marked a critical transition in the formation of the early Islamic state, requiring effective financial governance to preserve political stability and social cohesion. Although Abu Bakr As-Siddiq's fiscal policies have been widely discussed from economic perspectives, their contribution to Islamic civilization and relevance to contemporary Islamic Business Management remain underexplored. This study aims to analyze the state financial management model implemented during Abu Bakr's caliphate from the perspective of Islamic civilization and examine its relevance to Islamic Business Management. A qualitative historical approach was employed through document analysis of classical historical sources and recent journal articles published between 2020 and 2025. The data were analyzed using thematic analysis and source triangulation to ensure the credibility of historical interpretation. The findings reveal that Abu Bakr established a financial governance model based on amanah (trustworthiness), justice, accountability, consultation, and public welfare, which strengthened political legitimacy, institutional continuity, and social integration during the formative period of Islamic civilization. This study concludes that these governance principles remain relevant for contemporary Islamic Business Management, particularly in promoting ethical leadership, corporate governance, financial accountability, and sustainable organizational management, while bridging Islamic Civilization Studies and Islamic Business Management through a historical governance perspective.